2019
DOI: 10.1017/s0007114519001946
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous production ofn-3 long-chain PUFA from first feeding and the influence of dietary linoleic acid and theα-linolenic:linoleic ratio in Atlantic salmon (Salmo salar)

Abstract: Atlantic salmon (Salmo salar) possess enzymes required for the endogenous biosynthesis of n-3 longchain polyunsaturated fatty acids (LC-PUFA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), from a-linolenic acid (ALA). Linoleic acid (LA) competes with ALA for LC-PUFA biosynthesis enzymes leading to the production of n-6 LC-PUFA, including arachidonic acid (ARA).We aimed to quantify the endogenous production of EPA and DHA from ALA in salmon fed from first feeding on diets that contain no EPA and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Sissener et al (14) found a positive correlation between dietary 18 : 2n-6 and FAPV of DHA in Atlantic salmon (dietary DHA at 2•3-2•8 in % of total FA). However, a recent trial feeding Atlantic salmon fry/parr an EPA and DHA-free diet from start feeding found that high dietary 18 : 2n-6 inhibited the biosynthesis of long-chain PUFA (46) . The present experiment did not show any effect of dietary 18 : 2n-6 on DHA FAPV.…”
Section: Discussionmentioning
confidence: 99%
“…Sissener et al (14) found a positive correlation between dietary 18 : 2n-6 and FAPV of DHA in Atlantic salmon (dietary DHA at 2•3-2•8 in % of total FA). However, a recent trial feeding Atlantic salmon fry/parr an EPA and DHA-free diet from start feeding found that high dietary 18 : 2n-6 inhibited the biosynthesis of long-chain PUFA (46) . The present experiment did not show any effect of dietary 18 : 2n-6 on DHA FAPV.…”
Section: Discussionmentioning
confidence: 99%
“…This was comparable to that of the aqueous enzymatic extracted oil (64.1 g/100 g) and ultrasound-assisted hexane extracted oil (61.9 g/100 g) . It has been reported that after a series of metabolic activities in the body, ALA could finally produce eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) , which are especially beneficial to human health 24) . The common commercial oils contain relatively lower content of ALA, such as soybean oil (5.0-11.0 g/100 g) , rapeseed oil (5.0-13.0 g/100 g) and peanut oil (<0.3 g/100 g) 25) .…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…In this respect, it seems that all our experimental feeds provided enough EFA for growth of salmon (from diets or biosynthesis pathways) because they had no effects on the SR of fish 12 and also did not show typical deficiency signs of EFA. 6 The fact that proportions of liver lipid classes were not affected by experimental diets (Table S3) could suggest that fish oil elimination, minimizing EPA + DHA, and alteration of LNA/ALA ratio in salmon diets did not have adverse effects on liver lipid classes. This is in agreement with the liver data in Atlantic salmon reported by Katan et al, 13 who used 0.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Interestingly, the DHA to EPA ratio showed that endogenous production of EPA and DHA was not constant. Sprague et al 6 mentioned that a possible mechanism for the effect of dietary LNA on the ratio of DHA to EPA is that increased LNA would increase competition with ALA for the LC-PUFA pathway (Δ6 FADs) and this could especially affect the production of EPA, but not DHA production because of being produced indirectly from EPA (at least via two pathways; Figure 2). Another reason may be related to higher production and accumulation of EPA (than DHA) in PLs and NLs especially with low dietary levels of EPA + DHA as clearly shown in Figure 3a,b.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation